2016
DOI: 10.1038/npjgenmed.2016.36
|View full text |Cite
|
Sign up to set email alerts
|

Missense-depleted regions in population exomes implicate ras superfamily nucleotide-binding protein alteration in patients with brain malformation

Abstract: Genomic sequence interpretation can miss clinically relevant missense variants for several reasons. Rare missense variants are numerous in the exome and difficult to prioritise. Affected genes may also not have existing disease association. To improve variant prioritisation, we leverage population exome data to identify intragenic missense-depleted regions (MDRs) genome-wide that may be important in disease. We then use missense depletion analyses to help prioritise undiagnosed disease exome variants. We demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 36 publications
2
53
0
Order By: Relevance
“…To quantify genetic tolerance in genes, protein domains and domain homologues (Figure ) we made use of the d N / d S score rather than other well‐established tolerance scores such as pLI (Lek et al., ), RVIS (Petrovski et al., ), and subRVIS (Gussow et al., ). The d N / d S metric was originally intended for detecting selective evolutionary pressure in protein‐coding regions and genomes (Li, Wu, & Luo, ; Yang & Bielawski, ; Yang et al., ), and has previously been used by us and others to measure genetic tolerance and predict disease genes (Ge, Kwok, & Shieh, , ; Gilissen et al., ). Our choice for this score was motivated by the fact that the mentioned tolerance scores typically capture a more general notion of tolerance to genetic variation and are not designed to measure tolerance for any specific genic region of interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To quantify genetic tolerance in genes, protein domains and domain homologues (Figure ) we made use of the d N / d S score rather than other well‐established tolerance scores such as pLI (Lek et al., ), RVIS (Petrovski et al., ), and subRVIS (Gussow et al., ). The d N / d S metric was originally intended for detecting selective evolutionary pressure in protein‐coding regions and genomes (Li, Wu, & Luo, ; Yang & Bielawski, ; Yang et al., ), and has previously been used by us and others to measure genetic tolerance and predict disease genes (Ge, Kwok, & Shieh, , ; Gilissen et al., ). Our choice for this score was motivated by the fact that the mentioned tolerance scores typically capture a more general notion of tolerance to genetic variation and are not designed to measure tolerance for any specific genic region of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the authors found that intolerance to genetic variation within genic sub-regions significantly correlates with reported pathogenic mutations. These patterns of region-specific variation in genetic tolerance were also used by Ge et al (2016) to detect missense-depleted regions to confirm the pathogenicity of individual variants of unknown significance.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we measured tolerance to variation as the ratio of missense over synonymous variation ''d N =d S ,'' which has been used by us and others previously for predicting disease genes. 2,41,42 We downloaded all PASS-filtered single nucleotide variants (SNVs) from ExAC (n ¼ 9,035,134) and constructed a ''d N =d S '' measure by counting the unique missense SNVs missense obs , and the unique synonymous SNVs synonymous obs , while correcting for sequence composition using the total possible unique missense and synonymous SNVs (missense bg and synonymous bg respectively): d N =d S ¼ ððmissense obs =missense bg Þ=ðsynonymous obs = synonymous bg ÞÞ (Table S16). Based on calculations of these scores for the sets of 116 NHI, and 183 HI genes, we indeed find that genes with mutations acting through a NHI mechanism are significantly more intolerant to missense variation than genes with mutations acting though a HI mechanism (p ¼ 2.24e-03; permutation test, Figure 2).…”
mentioning
confidence: 99%
“…Discussion of these roles is beyond the scope of this review (see textbox for some open questions). Based on its fundamental and diverse roles, COPI dysfunction culminates in disease (Bettayeb et al, 2016a,b;Ge et al, 2016;Hamada et al, 2004;Izumi et al, 2016;Watkin et al, 2015;Xu et al, 2010). Here, we address the different stages of COPI vesicle biogenesis and revisit them in the context of striking recent developments in elucidating the structure of the COPI coat.…”
Section: Introductionmentioning
confidence: 99%